Toenail metal concentration as biomarker of exposure to heavy metal in drinking water of the Pasir Mas district, Malaysia - Ab Razak, Nurul Hafiza (2016)
Drinking water consumed by population is generally from piped water to the house, public pipe or standpipes, boreholes, protected dug wells, protected springs and rainwater collection. Population in Pasir Mas use tap water as the main source of drinking water. Even the water sources has been treated before distributed to consumers, drinking water is still contaminated by heavy metal due to less efficient treatment system or leach out from plumbing systems. The first objective of this study was to ascertain the level of knowledge, attitude and practice (KAP) regarding heavy metal contamination of Pasir Mas drinking water. The second objective was to determine the concentration of heavy metals (Al, Cr, Cu, Fe, Ni, Pb, Zn, and Cd) in drinking water and toenail from Pasir Mas. The third objective was to identify potential sources of heavy metal in drinking water from Pasir Mas. The next objective was to investigate correlation between heavy metal (Fe, Cu and Pb) concentration in drinking water and toenail. This study also identified the associations of confounders with heavy metal in toenail. Finally, this study evaluated health risks for heavy metal exposure via drinking water among respondents from Pasir Mas District. Stratified random sampling was used to select 214 respondents in Pasir Mas. A set of modified questionnaire were administered to the respondents to achieve the first objective. Then, analysis of heavy metal in drinking water were carried out using Graphite Furnace Atomic Absorption Spectrophotometry (GF-AAS) and heavy metal in toenail were analysed using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Statistical analysis involved in this study were cluster analysis and Mann-Whitney U test for the third objective. Spearman correlation analysis was carried out to investigate correlation between heavy metal (Fe, Cu and Pb) concentration in drinking water and toenail. Lastly, Multiple Linear Regression (MLR) was carried out to identify the associations of confounders with heavy metal in toenail. Pasir Mas population has good knowledge (80%), less positive attitude (93%), and good practice (81%) towards heavy metal contamination in drinking water. Heavy metal (Al, Cr, Cu, Fe, Ni, Pb, Zn, and Cd) analysed in this study was found to be under the permissible limit of drinking water quality set by the Malaysian Ministry of Health. Concentrations of heavy metal in toenail from Pasir Mas population were 35.29 ± 39.22 μg/g (Fe), 3.89 ± 2.08 μg/g (Cu) and 0.30 ± 0.34 μg/g (Pb). Cluster analysis (CA) was performed to classify the heavy metal on the basis of the similarities of their physical and chemical properties into clusters for purposes of source apportionment. Cluster analysis of heavy metal in drinking water showed three clusters which were Ni, Pb and Cr (C1), Cu, Zn and Fe (C2) and Al (C3). Thus, the cluster analysis indicated three main possible sources of heavy metal in drinking water. Cluster 1 (Ni, Pb and Cr) might originate from heavy metal leaching from galvanised iron and mild steel pipeline. Cluster 2 (Cu, Zn and Fe) might originate from corrosion of pipeline and occurrence of the heavy metal in Kelantan river water which were affected by agricultural run-off. Cluster 3 (Al) was likely to originate from usage of alum in conventional water treatment system. Mann- Whitney U test has shown that heavy metal concentration of Pb, Fe, Cu and Zn were significantly (p<0.05) different at house and distribution tanks which indicated that plumbing material were the source of the heavy metal in drinking water sample from Pasir Mas District. This study also showed no significant correlation between heavy metal (Fe, Cu and Pb) in drinking water and toenail. This study found confounder associated with heavy metal in toenail is dietary intake (cockles, sandwich bread and marine fish). A total of 17.5% variation in Fe concentration in toenail was explained by Cu in toenail and dietary intakes of cockles and sandwich bread. Model for Cu showed Fe concentration in toenail and cockles intake had accounted to 13.5% variation in Cu concentration in toenail. Dietary intakes of sandwich bread and marine fishes had 14.2% of variance for Pb concentration in toenail. Health Risk Assessment conducted in this study showed no potential non-carcinogenic and carcinogenic risks from the intake of heavy metal through drinking water. In conclusion, this study provided information on KAP of the Pasir Mas population towards heavy metal in drinking water. Output of this study provided information that conventional treatment system is adequate to treat the Kelantan river water to be used as drinking water. This study also showed that pipeline material of galvanised pipes, mild steel and PVC could be the source of heavy metal in treated drinking water supplied to population in Pasir Mas. Output of this study provided evidence that toenail was a less efficient biomarker to reflect heavy metal (Fe, Cu and Pb) exposure through drinking water ingestion pathway. Lastly, this study provided information to fulfil the knowledge gap on health risk assessment (HRA) regarding heavy metal exposure through ingestion of drinking water. This information could be beneficial for decision makers and authorities to improve drinking water quality and management in the future.